On Mergers in Consumer Search Markets - Maarten C.W. Janssen; Jose Luis Moraga-Gonzalez (Tinbergen Institute, 2007)
We study mergers in a market where N firms sell a homogeneous good and consumers search sequentially to discover prices. The main motivation for such an analysis is that mergers generally affect market prices and thereby, in a search environment, the search behavior of consumers. Endogenous changes in consumer search may strengthen, or alternatively, offset the primary effects of a merger. Our main result is that the level of search costs are crucial in determining the incentives of firms to merge and the welfare implications of mergers. When search costs are relatively small, mergers turn out not to be profitable for the merging firms. If search costs are relatively high instead, a merger causes a fall in average price and this triggers search. As a result, non-shoppers who didn't find it worthwhile to search in the pre-merger situation, start searching post-merger. We show that this change in the search composition of demand makes mergers incentive-compatible for the firms and, in some cases, socially desirable.
Keywords: D40; D83; L13; 330; consnmer search; mergers; price dispersion; Fusion; Konsumentenverhalten; Preisspanne; Informationskosten; Unvollkommener Markt; Suchtheorie; Theorie